Digital Innovation Based Business Development Strategies for MSMEs in the Industry 4.0 Era - Ardiansyah, Nisa; Aurellia, Raihana Zahra; Anatasya, Wahyu; S, Petra Carolline Putri; Hakim, Haris Al; N, Rusdi Hidayat (Journal of Micro, Small and Medium Enterprises, 2025)
While small and medium-sized enterprises (MSMEs) are at the core of the nation's economy, they still face a number of challenges when expanding, especially during the Industrial Revolution 4.0, which requires them to adapt to digital technology. Small and medium-sized businesses (MSMEs) have a great opportunity to increase competition, operating efficiency, and market reach through digital innovation. In this article, we will discuss various ways to grow MSME businesses using digital innovations such as e-commerce, digital payment systems, the use of social media, and business process automation. This review was conducted through a qualitative descriptive literature study method. The results show that strategically and sustainably applying digital innovations can scale up MSME businesses and increase their resilience to external shocks. However, this progress must be accompanied by policies that support MSMEs, improved digital literacy, and infrastructure support. This article provides conceptual and practical contributions for MSME actors, government, and academics in designing adaptive and sustainable business development models in the digital era.